Sustainable production of hierarchically porous carbon from lignin-acrylic acid copolymers - Pourbaba, Reza; Abdulkhani, Ali; Rashidi, Alimorad; Ashori, Alireza; Braving, Ariana (Springer, 2024)
Microporous carbon adsorbents with high surface area and porosity were synthesized from lignin using an acrylic acid pretreatment strategy. Lignin was grafted with acrylic acid via hydrothermal treatment to introduce carboxyl groups, as verified by NMR and FT-IR spectroscopy. The incorporated carboxyls enabled ion exchange reactions between lignin and potassium during subsequent potassium hydroxide (KOH) activation. This optimized the dispersion of potassium, allowing effective activation even at low KOH levels. The effects of process parameters, including acrylic acid content, hydrothermal time, and KOH ratio, were investigated. Optimal conditions of 5 wt acrylic acid and 6 h hydrothermal reaction produced a carbon adsorbent with exceptional Brunauer–Emmett–Teller (BET) surface area of 1708 m2/g and pore volume of 0.82 cm3/g at a lignin:KOH:acrylic acid ratio of 1:0.5:0.05. Characterization by FE-SEM, XRD, EDS, and Raman spectroscopy confirmed the successful synthesis of an optimized microporous carbon material. The carbon exhibited an outstanding lead ion adsorption capacity of 371 mg/g by Langmuir modeling. Adsorption kinetics followed pseudo-second-order, indicating chemisorption as the rate-controlling step. Thermodynamic analysis revealed the endothermic nature of lead adsorption, further enhanced at higher temperatures. Overall, the acrylic acid pretreatment approach enabled sustainable production of high surface area microporous carbon adsorbents from lignin using minimal KOH activation. The adsorbents demonstrated tremendous potential for removing lead ions via chemisorption mechanisms.